Геохимия болотных вод нижней части бассейна Томи (юг Томской области); Геохимия; № 4 - Шварцев С. Л. Степан Львович; Серебренникова О. В. Ольга Викторовна; Здвижков М. А. Михаил Александрович; Савичев О. Г. Олег Геннадьевич; Наймушина О. С. Ольга Сергеевна (2012, 2012)
Заглавие с экрана